The Use of Conceptual Metaphors in Expressing Love in Song’s Lyrics Titled “Best Part” by Daniel Caesar Featuring H.E.R. - Pakpahan, Jonathan Arif; Heriyati, Nungki; Nungki, Nungki (Mahadaya: Jurnal Bahasa, Sastra, Dan Budaya, 2025)
This research explores how conceptual metaphors are used to express love in the song’s lyric titled “best part” by Daniel Caesar featuring H.E.R. the source and target domain that refers to a lover or describe a lover is the main goal of this research. This research uses descriptive qualitative approach. From the analysis, six conceptual metaphors were identified, each comparing a partner or significant other with essential or comforting elements, those are coffee, sunshine, a star, the best part of a movie, and Tylenol. These conceptual metaphors convey or expresses love by highlighting the singer’s deep emotional connection, appreciations, and reliance to their partner. They emphasize how the partner or significant other brings meaning, joy and support to the singer’s life. The findings also show that conceptual metaphors play a crucial role in simplifying abstract emotions, building more relatable and impactful lyrics for the listener. Keywords: Conceptual metaphor, Lyrics, Love